New Trends of Public Administration and its Impacts on Regional Development - Batool, Sarfraz (2020)
Many experts of developmental studies are convinced that public administration is an effective tool for socio-economic and political development at national, regional and international level. However, conventional style of public administration is unable to cope with the needs and challenges of development in the age of liberal economic order. During last three decades, major reforms have been done in the structures of public administration worldwide to make it vibrant and efficient to boost up the process of development at local, regional and global level. This paper discusses three major points: first what is the relationship of public administration with socio-economic development? Second, why the reforms are needed in the structure, procedure and practice of public administration in the era of modern development? Finally, how vibrant and efficient public administration can serve as an effective tool for regional development? The paper finds that after the digitalization of public administration, the process of regional development will be accelerated due to increase in regional and global connectivity of public and private sector.